SECTARIANISM IN ISLAM: THE STUDY OF KHAWARIJ AND MAJLIS MUJAHIDIN INDONESIA - Muhammad Sairi (UIN Syarif Hidayatullah Jakarta, 2021)
Abstract. Basically, the study of sectarianism refers to the problem of understanding within a certain group, school, or belief. However, in its development this term has developed and is almost always associated with the study of the fanaticism of the madzhab (al-ta’asshubiyyah) and political partisans (al-hizbiyyah). Therefore, sectarianism as an ideology or ism often creates negative-destructive consequences, especially by creating a heroic attitude in defending the group as well as opposing other groups who are not in the same direction. In fact, not infrequently it creates radical attitudes on other parties in the name of the truth (read: religion) which they believe. This paper discusses sectarianism in Islam by using